Improving the Regional Investment Policy Using an Integrated Programme of Rural Development - Esina, Yulia L.; Stepanenkova, Natalya M. (Economy of Regions, 2021)
Nowadays, authorities pay more attention to the problems of regional development, reduction of socio-economic inequality of rural and urban areas, improvement of the efficiency of the agriculture, and degradation of rural population. All those issues are considered in the state programme of the Russian Federation «Integrated Development of Rural Areas». Thus, we assess whether the goals set in the state programme were achieved and substantiate the priority areas for future investment. We hypothesise that the achievement of the goals set at the federal level depends on the quality and implementation of rural development programmes adopted at the regional level. We revealed the uneven economic, social, infrastructural development, investment imbalances in various areas, changing sources of funding in the process of problem solving, lack of clear goals of agricultural policy and statistical information on its indicators of achievement. Classification and generalisation of views of other researchers on the topic allowed us to scientifically prove the existence of social problems, income inequality between urban and rural population, poor infrastructure and insufficient funds allocated to support rural areas. Further, we developed an algorithm for comparing the main parameters of rural development in Lipetsk oblast and nearby regions, complying with the criteria set by the federal programme. Using this algorithm, we assessed the effectiveness of the measures taken. We identified the most sensitive problems to be solved for reducing territorial inequality and the lag in socio-economic development, and increasing the competitiveness and attractiveness of Lipetsk oblast in terms of living conditions and investment. Finally, we proposed and substantiated the main directions of improving the regional investment policy. Regional authorities can use the research results in the implementation of the rural development policy.